266 “How will I get there” Institutional guidance and support for research-related transportation to engage diverse participants from underrepresented populations - Nicholas Prestayko; Aleksandra Zgierska (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Transportation is a barrier to research participation, especially for participants from disadvantaged backgrounds. Our goal was to review existing policies and create recommendations for institutional guidance on research-related transportation to support a long-term birth cohort study. METHODS/STUDY POPULATION: To summarize existing institutional policies on research-related transportation (i.e., transportation of participants or research staff travel to/from research activities), we requested and, in addition, searched for such policies across 28 sites involved in the NIH HEAL Initiative’s HEALthy Brain and Child Development (HBCD) study. The HBCD study plans to enroll 7,500 pregnant/postpartum persons, follow their children and families long-term, and assess factors influencing brain and child development. The obtained policies were then summarized, followed by identification of gaps in their recommendations and guidance. RESULTS/ANTICIPATED RESULTS: Outreach to the HBCD study sites and search of their institutional websites resulted in identification of 6 institutional policies or other guidance related to research-related transportation across five HBCD study sites. Three policies/guidance related to ride-share programs in research, two related to reimbursement for participant travel, and the fifth was about car seats. Through the online search, we also found policies or written guidance about employee-related transportation within 15 HBCD study sites in total; they largely pertained to employee business travel and did not specifically address research-related transportation. DISCUSSION/SIGNIFICANCE: To optimally support research teams, participants, and to promote the enrollment and retention of participants from diverse backgrounds, it is critical for research institutions to develop and implement guidance on research-related transportation and remove barriers to participation in research.